Agricultural Education and Practices for Making Organic Fertilizer in Sempu Hamlet, Cowek Village, Purwodadi District, Pasuruan Regency - Rohma, Novia Nur; Syaikhudin, M. Syaikhudin (Communautaire: Journal of Community Service, 2022)
Organic fertilizers are fertilizers derived from dead plants, animal dung, other organic wastes that have gone through an engineering process, in solid or liquid form, can be enriched with minerals and microbes that are useful for increasing the nutrient content and soil organic matter and improving physical properties. soil chemistry and biology. The majority of the people of Cowek Village, especially Sempu Hamlet, make a living as farmers. They rely on paddy fields and dry fields which are mostly planted with corn. Farmers still use inorganic fertilizers (chemical) in large doses without being balanced with organic fertilizers. The purpose of this activity is to increase the community's sense of responsibility to protect the environment and also provide understanding to the community about how to make organic fertilizer from animal waste. The method of service is to carry out socialization and agricultural education as well as the practice of making organic fertilizers. The PAR 2022 Real Work Lecture activity has been successfully carried out with the output of raising public awareness about the importance of maintaining environmental cleanliness and the use of animal waste into organic fertilizer.